(3GdJMbjb aj TQGA GdQbjbs
(3ChdgG (B:s
(3GdMeO ddg HLejY eMGeOg adjS Ndb ef GdCMjG fYdeg ef Pi MLGR hdG TGe hdGjef GdGhge TQcGA ai ahGVd s
(3BNQgG (B:s
(3Gdae aeUfY GdYhO GdQWH hGdcSaQI hGdeVeVI HGdNeQ heG GdhQO hGdYhO GdefbhY GdCSfGf s
(3HChdg agQSs
(3Ydjg GdYOjO ef GdJedcGJs
(3fSNI KGfjI WHb GdCUd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs